(untitled) (Journal of Economic Research & Business Administration, 2026)
The present study is aimed at studying the institutional system of regulation and support of small and medium-sized businesses (SMEs) in the Republic of Kazakhstan, as well as at identifying factors determining the effectiveness of government policy in this area. The purpose of the work is to comprehensively study the role of government agencies, development institutions and infrastructure organizations that form mechanisms to support entrepreneurship. Special emphasis is placed on the analysis of the functional role of the Ministry of National Economy, the Atameken National Chamber of Entrepreneurs, the Joint Stock Company "Entrepreneurship Development Fund "Damu" and regional centers that provide entrepreneurs with access to financial, consulting and educational tools. The scientific significance of the study lies in the systematization of existing approaches to the institutional regulation of SMEs and the identification of key barriers limiting the effectiveness of support programs. The research methodology is based on an institutional analysis, a comparative review of regulatory documents, as well as statistical data on the dynamics of SME development, its contribution to GDP, the structure of entities and the number of employees. The results revealed the main group of problems, including duplication of functions between institutions, complexity of support procedures, insufficient digitalization of services, and limited access to financing for microbusiness. Based on the analysis, the directions of optimization of the institutional model are proposed, including the integration of digital platforms, the redistribution of the functions of development institutions and the expansion of non-monetary support tools. The practical significance of the work lies in the formation of recommendations aimed at increasing the availability of government support measures and strengthening the role of SMEs in the economy of Kazakhstan. Keywords: small and medium-sized enterprises, government support, institutional structure, regulation, SME development.